Feeding, reproduction and population structure of Pimelodus maculatus Lacépéde, 1803 (Teleostei, Siluriformes, Pimelodiae) from Paraná basin: a review - Ramos, Igor Paiva [UNESP]; Magnoni, Ana Paula Vidotto [UNESP]; Brandão, Heleno [UNESP]; David, Gianmarco Silva; Carvalho, Edmir Daniel [UNESP] (My University, 2011)
The aim of this review is to present data regarding the feeding, reproduction, population structure of Pimelodus maculatus (Siluriformes, Pimelodidae). Forty two scientific manuscripts from 24 journals and 17 book chapters were analyzed from the years of 1951 to 2009. This species has type locality at the River Plate, Argentina, and have a wide geographical distribution in South America, being one of the most abundant species of the Paraná River basin, and an important constituent of the fish fauna of streams, rivers, and lentic waters (including large reservoirs). P. maculatus is characterized as a omnivorous species, with a large plasticity of feeding habits, being able to feed on vegetal matter, invertebrates, insects and fish. Due to this opportunistic behavior, some authors argue that P. maculatus is able to explore almost all trophic levels of aquatic freshwater ecosystems. In addition, it is considered a migratory species, able to perform migrations of up to 1,000 km; however, the physiological demands related to reproductive success are much smaller. The period of reproduction varies slightly according to the environment, but is always from October to March, a period corresponding to higher rainfall in the region of the Upper Paraná basin. Based on all information revised, P. maculatus has characteristics that allow it to adjust in different manners to environmental conditions, in different locations in natural geographical distributions.

O objetivo desta revisão é apresentar dados referentes à alimentação, reprodução e estrutura populacional de Pimelodus maculatus (Siluriformes, Pimelodidae). Foram analisados 42 artigos científicos oriundos de 24 periódicos e 17 capítulos de livros entre os anos de 1951 a 2009. Esta espécie tem como localidade tipo o rio da Prata, Argentina, tendo ampla distribuição geográfica na América do Sul. Ainda, é uma das espécies mais abundantes na bacia do rio Paraná e um importante constituinte da ictiofauna de riachos, rios e represas. P. maculatus é caracterizada como espécie de hábito alimentar onívoro, com grande plasticidade alimentar, podendo se alimentar de vegetais, invertebrados, insetos e peixes. Devido a este comportamento oportunista, alguns autores relatam que P. maculatus pode explorar todos os níveis tróficos dos ecossistemas aquáticos. Também, é considerada uma espécie migratória, podendo realizar migrações de até 1.000 km. Entretanto, suas necessidades fisiológicas para obter sucesso reprodutivo são muito menores. O período de reprodução apresenta pouca variação de acordo com o ambiente, sendo sempre entre os meses de outubro a março, período chuvoso na região da bacia do alto Paraná. Baseado nestas informações, concluí-se que P. maculatus possui características que permitem um bom ajuste para diferentes condições ambientais, em diferentes locais de sua distribuição geográfica natural.
Keywords: Upper Paraná River basin; Ecology; Feeding; Reproduction; Growth; Mandiamarelo; Bacia do alto rio Paraná; Ecologia; Alimentação; Reprodução; Crescimento; Mandi-amarelo